Analysis of PQ waveform for optimum data transmission over IEC 61850 communication standards - Yunus B.; Li H. (2023)
Power-quality phenomena such as voltage sag are observed at several substations to obtain an overview of the general network state and quality of power supply. Presently, collections of data from disturbance recorders involved long and tedious downloading process through telephone line. Usage of internet protocols consumed bandwidth and causes traffic congestion of the wide area network. This paper describes an integrated application of power quality monitoring system for a modeled substation over the IEC 61850 standard. The application used wavelet compression technique for transmission of voltage sag waveform over IEC 61850 standard and then IP network or Internet to a control centre. Analysis done shows that the correct selection of mother wavelet can achieve over 90% data compression ability while preserving all significant power quality features required for power quality waveform analysis. Results also shows that the optimum compression can be achieved at a predetermined communication channel speed by finding the suitable sampling frequency. For transferring the data through a 19.2 kbps channel, the optimum efficiency is achieved by using 97% compression at a sampling frequency of 7 kHz. 2008 IEEE.